Design method of frequency similarity relation for shaking table model test - Guo, Mingzhu; Chen, Xudong; Zeng, Jinyan (Frontiers in Earth Science, 2023)
It is very important to determine the dynamic similarity relation in the shaking table model test. The accurate dynamic similarity relation can make the model reflect the dynamic characteristics of the prototype to the greatest extent. This paper describes the principle of similarity design for shaking table model test and reviews the related literature.According to the different research objects and purposes, four common similarity design methods including separation similarity method, artificial mass method, less artificial mass method and ignoring gravity method are summarized.Analysis of the shortcomings of the method of deriving frequency compression ratio from static factors in the design of seismic wave similarity relation.The Duhamel integral analytic expression of the structure motion equation under earthquake is analyzed. The seismic response of the structure is closely related to the natural vibration frequency of the structure.A design method using frequency as input seismic wave similarity design control quantity is proposed.The natural vibration frequencies of the prototype and the model are studied by means of the Gonza landslide field ground pulsation test and the model white noise excitation.A new frequency compression ratio design scheme is given from the perspective of dynamic similarity.It is of great reference significance to optimize the dynamic similarity design of shaking table model test and improve the accuracy of test results.